A novel single virus infection system reveals that influenza virus preferentially infects cells in g1 phase. - Ryuta Ueda (Public Library of Science (PLoS), 2013)
Background Influenza virus attaches to sialic acid residues on the surface of host cells via the hemagglutinin (HA), a glycoprotein expressed on the viral envelope, and enters into the cytoplasm by receptor-mediated endocytosis. The viral genome is released and transported in to the nucleus, where transcription and replication take place. However, cellular factors affecting the influenza virus infection such as the cell cycle remain uncharacterized. Methods/results To resolve the influence of cell cycle on influenza virus infection, we performed a single-virus infection analysis using optical tweezers. Using this newly developed single-virus infection system, the fluorescence-labeled influenza virus was trapped on a microchip using a laser (1064 nm) at 0.6 W, transported, and released onto individual H292 human lung epithelial cells. Interestingly, the influenza virus attached selectively to cells in the G1-phase. To clarify the molecular differences between cells in G1- and S/G2/M-phase, we performed several physical and chemical assays. Results indicated that: 1) the membranes of cells in G1-phase contained greater amounts of sialic acids (glycoproteins) than the membranes of cells in S/G2/M-phase; 2) the membrane stiffness of cells in S/G2/M-phase is more rigid than those in G1-phase by measurement using optical tweezers; and 3) S/G2/M-phase cells contained higher content of Gb3, Gb4 and GlcCer than G1-phase cells by an assay for lipid composition. Conclusions A novel single-virus infection system was developed to characterize the difference in influenza virus susceptibility between G1- and S/G2/M-phase cells. Differences in virus binding specificity were associated with alterations in the lipid composition, sialic acid content, and membrane stiffness. This single-virus infection system will be useful for studying the infection mechanisms of other viruses.